Potential of Electrospun Fibrous Scaffolds for Intestinal, Skin, and Lung Epithelial Tissue Modeling. Issue 4 (6th April 2023) - Gonçalves, Andreia M.; Leal, Filipa; Moreira, Anabela; Schellhorn, Tobias; Blahnová, Veronika Hefka; Zeiringer, Scarlett; Vocetková, Karolina; Tetyczka, Carolin; Simaite, Aiva; Buzgo, Matej; Roblegg, Eva; Costa, Pedro F.; et al.
Abstract : Tissue Modeling The proposed illustration is a visual metaphor of the electrospinning method, representing the weaving of the fibrous extracellular matrix of lung, intestine, and skin tissue. Similar to knitting, the electrospinning technique produces yarns with certain characteristics that can be arranged according to the tissue to be modeled. More details can be found in article number 2200104 by Yvonne Kohl and co‐workers.